Unique continuation for solutions of p(x)-Laplacian equations - Johnny Cuadro; Gabriel Lopez G. (Electronic Journal of Differential Equations, 2012)
We study the unique continuation property for solutions to the quasilinear elliptic equation $$ hboxdiv(|abla u|^{p(x)-2}abla u) +V(x)|u|^{p(x)-2}u=0quad hboxin Omega, $$ where $Omega$ is a smooth bounded domain in $mathbbR^N$ and $1<p(x)<N $ for $x$ in $Omega$.